Проблема зниження викидів забруднювачів у атмосферу в тепловій енергетиці України в контексті інтеграції ОЕС України в UСТЕ - Kostyukovskyi B.A.; Радченко; Shulzhenko S.V.; Nechaieva T.P.; Bilenko M.S.; Maksimets А.А. (General Energy Institute of the National Academy of Sciences of Ukraine, 2007)
Comparison of requirements to pollutant emissions in an atmosphere in thermal energy in European Union and in Ukraine. Accordance of current level of pollutant emissions in an atmosphere of the Ukrainian thermal power plants to the requirements of EU is analyzed, and the measures of gradual adduction of indexes domestic thermal power plants are matched to the EU requirements.